Control of p21Cip by BRCA1-associated protein is critical for cardiomyocyte cell cycle progression and survival. Issue 3 (20th August 2019) - Volland, Cornelia; Schott, Peter; Didié, Michael; Männer, Jörg; Unsöld, Bernhard; Toischer, Karl; Schmidt, Carla; Urlaub, Henning; Nickels, Katrin; Knöll, Ralph; Schmidt, Albrecht; Guan, Kaomei; et al.
Abstract: Aims: Identifying the key components in cardiomyocyte cell cycle regulation is of relevance for the understanding of cardiac development and adaptive and maladaptive processes in the adult myocardium. BRCA1-associated protein (BRAP) has been suggested as a cytoplasmic retention factor for several proteins including Cyclin-dependent-kinase inhibitor p21 Cip . We observed profound expressional changes of BRAP in early postnatal myocardium and investigated the impact of BRAP on cardiomyocyte cell cycle regulation. Methods and results: General knockout of Brap in mice evoked embryonic lethality associated with reduced myocardial wall thickness and lethal cardiac congestion suggesting a prominent role for BRAP in cardiomyocyte proliferation. αMHC-Cre driven cardiomyocyte-specific knockout of Brap also evoked lethal cardiac failure shortly after birth. Likewise, conditional cardiomyocyte-specific Brap deletion using tamoxifen-induced knockout in adult mice resulted in marked ventricular dilatation and heart failure 3 weeks after induction. Several lines of evidence suggest that Brap deletion evoked marked inhibition of DNA synthesis and cell cycle progression. In cardiomyocytes with proliferative capacity, this causes developmental arrest, whereas in adult hearts loss of BRAP-induced apoptosis. This is explained by altered signalling through p21 Cip which we identify as the link between BRAP and cell cycle/apoptosis. BRAP deletion enhanced p21 Cip expression, while BRAP overexpression in cardiomyocyte-specific transgenic mice impeded p21 Cip expression. That was paralleled by enhanced nuclear Ki-67 expression and DNA synthesis. Conclusion: By controlling p21 Cip activity BRAP expression controls cell cycle activity and prevents developmental arrest in developing cardiomyocytes and apoptosis in adult cardiomyocytes. Graphical Abstract: